2022
DOI: 10.3390/en15228752
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Model in Predicting Geomechanical Properties for Shale Formation: A Field Case in Permian Basin

Abstract: Due to complexities in geologic structure, heterogeneity, and insufficient borehole information, shale formation faces challenges in accurately estimating the elastic properties of rock which triggers severe technical challenges in safe drilling and completion. These geomechanical properties could be computed from acoustic logs, however, accurate estimation is critical due to log deficit and a higher recovery expense of inadequate datasets. To fill the gap, this study focuses on predicting the sonic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The application of machine learning and artificial intelligence involves several stages: data collection, data preparation, choosing the machine learning model, training, and testing of the model and validation [138]. Different researchers have applied artificial intelligence methods to predict geological [139], petrophysical [140], and geomechanical properties [141] and production and enhanced oil recovery methods' efficiency for shale and tight reservoirs [142,143]. A systematic review of the application of artificial intelligence by Syed et al [144] has shown an exponential increase in the publication of artificial intelligence applications to shale and tight reservoirs.…”
Section: Data-driven Modeling Approachesmentioning
confidence: 99%
“…The application of machine learning and artificial intelligence involves several stages: data collection, data preparation, choosing the machine learning model, training, and testing of the model and validation [138]. Different researchers have applied artificial intelligence methods to predict geological [139], petrophysical [140], and geomechanical properties [141] and production and enhanced oil recovery methods' efficiency for shale and tight reservoirs [142,143]. A systematic review of the application of artificial intelligence by Syed et al [144] has shown an exponential increase in the publication of artificial intelligence applications to shale and tight reservoirs.…”
Section: Data-driven Modeling Approachesmentioning
confidence: 99%
“…With the development of data processing technology and computer hardware and software facilities, the application of machine learning methods in shear wave velocity pre-diction has become a general trend [23][24][25][26][27][28]. The machine learning method has become one of the research hotspots in the oil and gas exploration industry.…”
Section: Introductionmentioning
confidence: 99%